(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this research, an experimental study was conducted on the solar box cooker manufactured with dimensions of (50*50*47cm). The solar box cooker was tested in Baghdad city from 7/4/2018 to 21/4/2018. Evaluation was carried out to test the performance of the solar cooker in two stages. The first stage included the solar cooker test in four cases through the test of the solar box cooker as fixed tracking and these two cases with and without a reflective mirror as another two cases. The results of the tests show that the best performance of the solar box cooker is when using the tracking and the reflective mirror in which the water temperature reached 109°C at 14:00 and also this test gives average water temperature during test period 81.6°C. The second stage the best case was selected (tracking solar box cooker with reflective mirror) to evaluate its performance according to the American Society of Agricultural Engineers standards. Therefore, the test of the solar box cooker was conducted with tracking and the reflective mirror for three days to reach a more accurate results in which 38 observations from those tests was selected. The results show that standardized cooking power equals to 56.09 W at a temperature difference of 50°C with r2 = 0.8318.